Biocidal poly (vinyl alcohol) films incorporated with N-halamine siloxane. (December 2018) - Li, Rong; Sheng, Junfeng; Cheng, Xiaoli; Li, Jing; Ren, Xuehong; Huang, Tung-Shi
Abstract: An N -halamine siloxane precursor γ-(β-hydroxyl-γ-5, 5- dimethylhydantoin)aminopropyltrithoxysilane (abbreviated as GHAPA) was synthesized in this study. GHAPA was mixed with PVA solution to prepare PVA/GHAPA cross linked film with an antimicrobial function. The obtained PVA/GHAPA cross linked film was characterized by TGA, DSC and XRD. Upon dilute household bleach treatment, the chlorinated PVA/GHAPA cross linked film could inactivate Staphylococcus aureus and Escherichia coli O157:H7 completely with concentrations of 4.57 × 10 7 cfu and 2.70 × 10 7 cfu within 5 and 10 min, respectively, and 99.9995% of Escherichia coli O157:H7 could be inactivated within 5 min. The antimicrobial results showed that the chlorinated films substantially outperformed the unchlorinated control samples. The biocidal films may serve as potential materials for food packaging and biomedical applications. Highlights: The N-halamine (GHAPA) modified PVA crosslinked film was prepared and characterized. The chlorinated PVA/GHAPA crosslinked film showed good efficiency against Escherichia coli and Staphylococcus aureus . The biocidal films may serve as potential materials for food packaging.